Weight Loss, Glycemic Control, and Cardiovascular Disease Risk Factors in Response to Differential Diet Composition in a Weight Loss Program in Type 2 Diabetes: A Randomized Controlled Trial - Rock, Cheryl L. (Diabetes Care, 2014)
OBJECTIVE: To test whether a weight loss program promotes greater weight loss, glycemic control, and improved cardiovascular disease risk factors compared with control conditions and whether there is a differential response to higher versus lower carbohydrate intake. RESEARCH DESIGN AND METHODS: This randomized controlled trial at two university medical centers enrolled 227 overweight or obese adults with type 2 diabetes and assigned them to parallel in-person diet and exercise counseling, with prepackaged foods in a planned menu during the initial phase, or to usual care (UC; two weight loss counseling sessions and monthly contacts). RESULTS: Relative weight loss was 7.4% (95% CI 5.7–9.2%), 9.0% (7.1–10.9%), and 2.5% (1.3–3.8%) for the lower fat, lower carbohydrate, and UC groups (P < 0.001 intervention effect). Glycemic control markers and triglyceride levels were lower in the intervention groups compared with UC group at 1 year (fasting glucose 141 [95% CI 133–149] vs. 159 [144–174] mg/dL, P = 0.023; hemoglobin A(1c) 6.9% [6.6–7.1%] vs. 7.5% [7.1–7.9%] or 52 [49–54] vs. 58 [54–63] mmol/mol, P = 0.001; triglycerides 148 [134–163] vs. 204 [173–234] mg/dL, P < 0.001). The lower versus higher carbohydrate groups maintained lower hemoglobin A(1c) (6.6% [95% CI 6.3–6.8%] vs. 7.2% [6.8–7.5%] or 49 [45–51] vs. 55 [51–58] mmol/mol) at 1 year (P = 0.008). CONCLUSIONS: The weight loss program resulted in greater weight loss and improved glycemic control in type 2 diabetes.